Peningkatan Efektivitas Kinerja Guru Pendidikan Agama Islam melalui Manajemen Evaluasi di SMA Negeri 7 Muaro Jambi - Fadlilah Fadlilah; Dian Nisa Istofa; Fitra Rantika Sari (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2021)
This research aims to find out the evaluation of the performance of Islamic religious education teachers at Sma Negeri 7 Muaro Jambi. This research uses descriptive qualitative research methods. Data is collected by observation, interview, and documentation. The results showed that Sma Negeri 7 Muaro Jambi implemented the implementation of teacher performance evaluation program management held in each semester. The evaluation and monitoring activities are carried out directly by the principal and the Ministry of Religious Affairs. The evaluation program for the performance management of Islamic religious education teachers went quite well. Teachers always report their performance results shown through the learning outcomes of students who continue to experience improvement.